Analysing the advantages of early contractor involvement. (1st January 2014) - Eadie, Robert; Graham, Matthew
Early contractor involvement (ECI), introduced by the Highways Agency in 2001 has commenced in Northern Ireland. The first five UK ECI schemes were investigated (Nichols Report, 2007) but there was an admission of limited piloting and research. Through an online survey and case study data this paper defines for the first time the success factors of the ECI procurement route against other UK Government approved procurement routes. It further shows cost savings of £59.3 m were achieved with an average saving per scheme of £5.4 m. ECI produces less time savings. The case studies confirm in larger schemes ECI supports risk management mitigating the costs accrued. However, there is often little benefit on smaller or low risk schemes. This research shows the negative issues relating to ECI costs and timescale stated by Owen (2009) are not shared by practitioners with initial opinions and statistics on the use of ECI being very positive.